Polyphased Variscan deformation in the Rehamna Massif: strong strain partitioning in dextral transpression - Kholaiq, Mariame (2018)
The Rehamna Paleozoic block is one of the major domains in the Moroccan Variscides. Although strongly studied since the classical fundamental works of Piqué (1972), Hoepffner (1974), Jenny (1974), and Michard (1976) there is no a geodynamical model able to compatibilize the observed deformation in all the Rehamna sectors. The three deformation phases recently defended (e.g. Chopin et al., 2014; Wernert et al., 2016) although explains the structural pattern of the meridional Rehamna sectors didn't fit well, either with the setentrional sector, or the Moroccan geodynamics, where a major N-S early compression is not common. The available data concerning the D1 structures shows that the NNE-SSW to N-S stretching lineations related to the D1 southward thrusting, which is well expressed in the western sectors, have an E-W general trend in the East of the Palaeozoic massif (Chopin, et al., 2014). This pattern shows that the thrusting kinematics is only a localized feature at the Rehamna scale. Thus it is possible to propose that the general dextral transpression along ENE-WSW trend that have emphasize in other sectors of Moroccan Variscides (e.g. Houari & Hoepffner, 2000; Dias et al., 2011) could also explain the Rehamna complex deformation. Due to a strong strain partitioning, the dextral kinematics tend to concentrate in the vicinity of major EW to ENE-WSW (e.g. AïnMellah Fault) while in the adjacent blocks a pure shear dominated transpression dominate, explaining the NNE-SSW to N-S pervasive folding at the Rehamna scale. In such a model, the southward D1thrusting and the E-W D2 folding (Chopin, et al., 2014; Wernert, et al., 2016) are the result of a corner effect related to space problems induced by the Neoproterozoic basement of Central Rehamna. Its stronger rheology give rise to a restraining problem leading the Ordovician of the Upper Metamorphic Unit to overlap the higher metamorphic southern sectors. The thrusting component decreases towards East where the sub-horizontal D1 and D2 mineral lineations predominate as expected in a dextral transpression. This shows that the dextral oblique collision between Laurentia and Baltica during tardi-Variscan deformation (Arthaud & Matte, 1975) is a long lasting deformation in the Moroccan Variscides.